Unsuspected Dengue as a Cause of Acute Febrile Illness in Children and Adults in Western Nicaragua. - Megan E Reller; Aravinda M de Silva; Jeremy J Miles; Ramesh S Jadi; Anne Broadwater; Katie Walker; Christopher Woods; Orlando Mayorga; Armando Matute (Public Library of Science (PLoS), 2016)
BACKGROUND:Dengue is an emerging infectious disease of global significance. Suspected dengue, especially in children in Nicaragua's heavily-urbanized capital of Managua, has been well documented, but unsuspected dengue among children and adults with undifferentitated fever has not. METHODOLOGY/PRINCIPAL FINDINGS:To prospectively study dengue in semi-urban and rural western Nicaragua, we obtained epidemiologic and clinical data as well as acute and convalescent sera (2 to 4 weeks after onset of illness) from a convenience sample (enrollment Monday to Saturday daytime to early evening) of consecutively enrolled patients (n = 740) aged ≥ 1 years presenting with acute febrile illness. We tested paired sera for dengue IgG and IgM and serotyped dengue virus using reverse transcriptase-PCR. Among 740 febrile patients enrolled, 90% had paired sera. We found 470 (63.5%) were seropositive for dengue at enrollment. The dengue seroprevalance increased with age and reached >90% in people over the age of 20 years. We identified acute dengue (serotypes 1 and 2) in 38 (5.1%) patients. Only 8.1% (3/37) of confirmed cases were suspected clinically. CONCLUSIONS/SIGNIFICANCE:Dengue is an important and largely unrecognized cause of fever in rural western Nicaragua. Since Zika virus is transmitted by the same vector and has been associated with severe congenital infections, the population we studied is at particular risk for being devastated by the Zika epidemic that has now reached Central America.